The Impact of Social Media for The Development of Da’wah in Indonesia - Mukti Ali; Avin Wimar Budyastomo (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2021)
This study aims to determine the impact of social media on the development of da'wah in Indonesia. Social media platforms commonly used by Indonesians, such as YouTube and Facebook, have significantly influenced the behavior and methods of delivering Islamic messages. In response to these changes, many scholars have adopted social media as a medium for da'wah. This research employs a descriptive qualitative approach by analyzing data collected through direct interviews with respondents. The findings indicate that social media has had a profound impact on the development of da'wah, enabling scholars to leverage technology for propagating Islamic teachings. The use of platforms such as YouTube and Facebook has made preaching more accessible and efficient, allowing scholars to reach broader audiences without the limitations of traditional methods. This study contributes to the understanding of how digital platforms transform traditional practices of da'wah, offering insights into the intersection of technology and religious communication. By highlighting the advantages and challenges of utilizing social media for da'wah, this research provides a foundation for further exploration of digital strategies in religious propagation.